L-Lactate Dehydrogenase-Bearing Bacteria Isolated from Shrimp Intestines as Potential Probiotics: an in Silico Study - Sujadi, Frentina Murti; Anjaini, Jefri; Setiyaningsih, Lilik; Wibowo, Dandi Setio; Nirwantono, Rudi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
L-Lactate Dehydrogenase (LLD) is a key enzyme in lactic acid metabolism, found in various bacteria, including lactic acid bacteria (LAB), which are potential probiotics for aquaculture. This study aims to analyze bacterial species isolated from shrimp intestines that possess LLD genes in their genomes and to examine the phylogenetic relationships of their LLD proteins, as a basis for assessing their potential as probiotics in the future. Bacterial species were collected through a literature review on isolates from shrimp intestines or culture media. After excluding pathogenic bacteria, the protein sequences fromthe included specieswere retrieved from NCBI using the Bio.Entrez and SeqIO modules in Biopython. Afterward, multiple sequence alignment (MSA) was performed using MEGA X software with the ClustalW algorithm, and a phylogenetic tree was constructed using the Maximum Likelihood method with 1000 bootstrap replications. In total, 23 bacterial species were identified from the literature, of which 15 were found to possess LLD protein sequences that were successfully retrieved. Phylogenetic analysis revealed groupings of bacteria based on thekemiripanof their LLD sequences. LAB species, such as Lactiplantibacillus plantarum and Pediococcus pentosaceus, clustered together, while species from the genus Bacillus and related taxa (e.g., Geobacillus thermoleovorans) formed a separate cluster. Overall, this sequence-based analysis successfully reconstructed the phylogenetic relationships among the identified bacteria based on their LLD sequences and highlighted groups of LLD-producing bacteria with potential probiotic applications in aquaculture. The findings provide a foundation for the further selection and development of promising indigenous lactic acid bacteria from shrimp intestines as probiotics.